The Myth of Prometheus in the Florentine Art of the Late 15th Century - Lopukhova, Marina A. (Actual Problems of Theory and History of Art, 2024)
Two panels by Piero di Cosimo dedicated to the story of Prometheus (1510–1515, Munich, Alte Pinakothek; Strasbourg, Museum of Fine Arts) are the first example of an expanded pictorial representation of this myth in the art of the Modern era. Precise attention to the motifs of the steal of fire from Apollo’s chariot and the revival of man created by Prometheus suggests that the artist interprets the myth in the comprehension of Giovanni Boccaccio and Marsilio Ficino: unlike ancient mythographers, the humanistic tradition emphasized the theme of the transfer of divine fire, which was associated with divine knowledge, rather than the theme of the punishment of the titan. The story of Prometheus stealing fire from Apollo’s chariot was first depicted by Filippino Lippi in a drawing from the collection of the Cabinet of Drawings and Prints of the Uffizi Gallery, which for stylistic reasons dates from the second half of the 1490s – early 1500s. The late dating does not allow us to directly connect it with Filippino’s large monumental projects, in particular with the frescoes of the Medici villa Spedaletto, as J. K. Nelson has posited on numerous occasions. Moreover, it cannot be ruled out that this theme had already gone beyond the Medici circle at the end of the 15th century and had become the property of enlightened clients who were seeking for intellectual alternatives to the religious dictate of Savonarola. Among them was the younger generation of the Strozzi family, under whose patronage Filippino completed the decoration of the family tomb in the church of Santa Maria Novella in Florence by 1502. As the aforementioned drawing its program bears the imprint of Ficino’s philosophy and appeals to the theme of sacred knowledge and the motif of divine fire. Since Piero di Cosimo’s panels, as A. Hoyer has recently shown, could have been created for the wedding of Filippo Strozzi the Younger and Clarice de’ Medici, which took place in 1508, it can be assumed that the original idea, which resulted in Lippi’s drawing, was born within the walls of their family palace. If the fresco “Prometheus Stealing the Celestial Fire” really existed, its recollection in the wedding painting ensemble of the first half of the 1510s can be interpreted as a sign of loyalty to the Medici family to which the bride belonged and which had returned to Florence.